Optical discrimination of threading dislocations in 4H-SiC epitaxial layer by phase-contrast microscopy. (6th June 2018) - Hattori, Ryo; Oku, Osamu; Sugie, Ryuichi; Murakami, Kazutsugu; Kuzuhara, Masaaki
Abstract: The superior nondestructive distinguishability of threading screw dislocations and threading edge dislocations in SiC epitaxial layers by phase-contrast microscopy using our optical system was demonstrated by comparing our experimental results with those obtained by conventional polarized light microscopy, photoluminescence topography, and KOH etching. It was confirmed that phase-contrast microscopy was more effective than polarized light microscopy in terms of the nondestructive discrimination of threading dislocations.